Optical measurements of phase transitions in difluorophenylazophenyl benzoate thermotropic liquid crystal with specific orientated fluorine atoms. (1st February 2019) - Zaki, A. A.
ABSTRACT: Phase transition temperature and optical properties of the special oriented fluorine atoms in difluorophenylazophenyl Benzoate Thermotropic Liquid Crystal nominated (III ) were studied and measured. Absorbance and transmittance in the visible region at room temperature for the compoundIII dissolved in methylene chloride of different concentrations were determined. The maximum absorbance for the compoundIII was in the blue region (447 nm) and the molar absorption coefficient was found to be 0.93 (L. mMol −1 .cm −1 ). The transition temperature was determined for the thermotropic LC compoundIII by using DSC, POM and modified spectrophotometer techniques. Nematic and smectic phases during the cooling process were observed. Ordinary and extraordinary refractive indices, birefringence, order parameter and the molecular polarizability were determined with different temperatures for the LC phases of compoundIII .